Polybius, the Hellenistic World and the cultural perspective: some lines of reflexion in the last twenty years (De Rebus Antiquis, 2020)
Our knowledge of some aspects of the Histories of Polybius has been significantly increased during the last two decades. In that sense, there have been some important developments regarding cultural aspects of the work, whose scope has been enabling to rethink during these years some classical assumptions about the relationship between Polybius,Rome and the Hellenistic world. We propose here to offer a quick analysis of the main three lines of study proposed by scholars, whose scope is considered, in effect, as a total replacement of the Achaean historian into the cultural universe of the Hellenistic world.
Keywords: Polybius; Hellenistic world; Rome; State of the Art Cultural Perspective